1990
DOI: 10.1007/bf01883752
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy for 21pter-q21: Case report and assignment of a DNA clone (Fr8-77) to the deleted segment

Abstract: SummaryA 4-month-old Japanese girl with partial monosomy 21 was described. The patient has craniofacial anomalies, a short neck, wide-set nipples, anal atresia, deformed feet, hypertonia, intrauterine growth retardation, and mental deficiency. RFA-and high-resolution GTG-banding chromosome analyses, and Southern-and slot-blot analyses interpreted her karyotype as 45,XX,-2,-21,+der(2)t(2;21)(q37.3;q22.1).The origin of this de novo translocation ascertained by analyses with both QFQheteromorphisms and a Fr8-77/B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Two cases had both CNS anomaly and midline facial defects such as cleft palate, cleft lip and flat nasal bridge (Fryns et al 1977;Wisniewski et al 1983). Abe et al (1990) reported a case with midline facial defects whose karyotype was 45, XX, -2, -21 , + der(2) t(2; 21) (q3.3; 822.1), but they did not mentioned CNS anomalies. Published cases of partial monosomy 21 mentioning CNS anomalies are shown in Table 1.…”
Section: Cytogenic Studiesmentioning
confidence: 99%
“…Two cases had both CNS anomaly and midline facial defects such as cleft palate, cleft lip and flat nasal bridge (Fryns et al 1977;Wisniewski et al 1983). Abe et al (1990) reported a case with midline facial defects whose karyotype was 45, XX, -2, -21 , + der(2) t(2; 21) (q3.3; 822.1), but they did not mentioned CNS anomalies. Published cases of partial monosomy 21 mentioning CNS anomalies are shown in Table 1.…”
Section: Cytogenic Studiesmentioning
confidence: 99%